LA DUREE POUR AMELIORER LES PERFORMANCES ET DISSIPER LES EFFETS NEGATIFS APRES LE STRETCHING PASSIF EST COMPRISE ENTRE 2 ET 15 MINUTES - Zerf, Mohammed; Mokkedes, Moulay Idrissii; Belfakroun, Abdellah; Mabrouki, Fatiha; Bengoua, Ali; Touati, Blidi (European Journal of Physical Education and Sport Science, 2016)
The objective of the present study was to investigate the effects of passive stretching alone on subsequent sprinting and jump performance. Two different stretching protocols: (a) static stretch (SS) to point of discomfort (POD); (b) a control warm-up condition without stretching were implemented with a prior aerobic warm-up and followed by dynamic activities. The control condition showed signficant differences (p = 0.05) for sprint, agility run, jump and measure of flexibility tests faster than the PS, POD condition. There were variable effects during the four phases of play. The performances were affected during the first time (D1), recuperation of muscular capacities in the second (D2), significant progresses in the third (D3) and stability with some perturbation in the last (D4). The lack of stretch-induced impairments may be attributed to the trained state of the participants or the amount of time used after stretching before the performance. Participants were either amateurs or regional level football athletes who trained 3–4 times a week with each session lasting; 90 minutes. Based on these findings and the literature, highly trained individuals or intermediary who wishes to implement static stretching should include an adequate warm-up and dynamic sportspecific
Keywords: passive stretching; performance; acute and chronic effects; dissipation